2010
DOI: 10.1590/s0102-311x2010000300019
|View full text |Cite
|
Sign up to set email alerts
|

Persistência dos sintomas de dengue em uma população de Uberaba, Minas Gerais, Brasil

Abstract: The clinical picture of dengue is characterized by a maximum duration of 14 days despite frequent complaints of longer symptoms. This study evaluated the occurrence of persistent symptoms (> 14 days) and its impact on daily life. A hundred eighteen patients were interviewed, and the main symptoms at diagnosis were mialgia (98.3%), fever (97.5%) and weakness (95.8%). The presence of at least a persistent symptom was related by 77 (65.2%) individuals of wich 10 (8.5%) described it as intense and lasting for 30 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 5 publications
3
5
0
4
Order By: Relevance
“…In contrast to a retrospective study previously published by our group, the prospective follow-up of patients in the present study provided more reliable information. Nevertheless, the prevalence of persistent symptoms was similar to that found in the previous retrospective study, 50-60% 10 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In contrast to a retrospective study previously published by our group, the prospective follow-up of patients in the present study provided more reliable information. Nevertheless, the prevalence of persistent symptoms was similar to that found in the previous retrospective study, 50-60% 10 .…”
Section: Discussionsupporting
confidence: 89%
“…Another specific chart was used during the outpatient follow-up to record the spontaneous complaints of the patients and then applying the objective inquiry about the presence of fever, headache, retro-orbital pain, myalgia, exanthema, prostration, arthralgia, nausea, vomiting, diarrhea, sleepiness, weakness, coryza, cough, hair loss, cognitive state, memory loss, reasoning problems and skin changes. The objective signs were extracted from a survey of symptoms reported in a previous study 10 . All visits were conducted by at least one of the two participating physicians.…”
Section: Methodsmentioning
confidence: 99%
“…This was based on a study by Teixeira et al . [26] . However, other studies have not found the same degree of post-acute consequences, and this requires further investigation [27] .…”
Section: The Estimated Daly Burden Of Dengue In Vietnammentioning
confidence: 99%
“…The current economic burden estimates do not account for the potential burden and income loss associated with symptoms that persist after resolution of the acute dengue episode, such as depression, profound fatigue, and weight loss 26 , 27 , 49 , 50 . A study in Mexico indicated that accounting for these persistent symptoms could increase the estimated economic burden of dengue by approximately 13% [27] .…”
Section: Data Gaps and Future Research Needsmentioning
confidence: 99%
“…Su etiología aún no se ha descrito con precisión, de la fase aguda, entre los cuales predominó el cansancio físico (65,6 %), la cefalea (37,5 %), el insomnio (31,3 %), el mareo, el cansancio mental (25 %) y el dolor muscular (18,8 %). Estos hallazgos coinciden con las observaciones registradas en otros estudios (16,(28)(29)(30). Al evaluar la presencia de fatiga física y mental después de la infección aguda por dengue, se evidenció que esta se mantuvo en 34,4 % de los pacientes durante su convalecencia, con síntomas como el Convalecencia de la infección del dengue Figura 2.…”
Section: Discussionunclassified